Social support in groups of mothers with different family status and its significance for satisfaction with work - Elżbieta Napora; Izabela Grzankowska; Małgorzata Anna Basińska (Nofer Institute of Occupational Medicine, 2018)
Background The purpose of the study was to determine to what degree social support is differentiated by family situation, with consideration of single motherhood as a difficult circumstance, and to establish if social support is significant for satisfaction with work in the studied group of mothers. Material and Methods The sample consisted of 421 mothers: 206 (49%) of them were in a formal or casual relationship, and the remaining 215 (51%) were single mothers. The sample was studied by means of the Berlin Social Support Scales (BSSS), and the Scale of Satisfaction with Work . Results The results showed that single mothers perceived and obtained significantly less social support than mothers in relationships, and they offered to their relatives much more protective support (p = 0.006). Satisfaction with work among mothers - regardless of the family status - grows if the mother receives more social support. The information support received by mothers in relationships is not significantly related to satisfaction with work; seeking that type of support by single mothers does not have a meaningful relationship with satisfaction with work, either. Moreover, regardless of the mothers' family status, satisfaction with work is significantly differentiated by each type of social support, except for protective support. Conclusions Social support is differentiated by the mothers' situation in the family and at work, and it has a different impact on single mothers from the impact on mothers in relationships. Med Pr 2018;69(5):497-507